The search for a national cinema / Gregory Wee Lik Hoo - Wee, Gregory Lik Hoo (UPENA, 2007)
A new cinema emerged in Malaysia at the turn of the new millennium. It was a different cinema which explored themes of alienation, racial boundaries and socio-political ideologies. Led by Amir Muhammad, James Lee, Ho Yuhang and Yasmin Ahmad, their films have signaled a level of maturity rarely seen before. Although their films have won international recognition and awards, they still face difficulties in obtaining government support through funding, and faces problems with censorship. This paper will look at the problems faced by these filmmakers. It will also look at how these new films are affecting the existing notions of what constitutes Malaysian cinema, and the new challenges that the existing film and funding policies face in building a 'new' national cinema.